APPLYING TEAM TEACHING TO IMPROVE STUDENTS’ ABILITY IN UNDERSTANDING ENGLISH NARRATIVE TEXTS - Saiful Akmal; Asrul Hadi (Englisia: Journal of Language, Education, and Humanities, 2015)
The title of this study is applying team teaching to improve students’ ability in understanding English narrative texts. The purposes of this study are to identify the advantages and to find out the strategies of applying team teaching to improve students’ ability in understanding English narrative texts. The population of this study is the first year students of SMAN 4 Banda Aceh, and the sample are an experimental class (X IA 2) and a control class (X IA 6). The total numbers of the samples are 66 students. This research was conducted on April, 2010. In collecting data, several techniques were used namely; observation, test, questionnaire and interview. According to data analysis, team teaching gave more advantages to improve students’ ability in understanding English narrative texts. Some advantages of team teaching to the first year students of SMAN 4 Banda Aceh; (1) Team teaching directed the students to focus on material, the method was not tedious and learning motivation had been increased by using it, so that their ability in understanding English narrative text had been increased. (2) The students who studied by using team teaching obtained higher score than the students who studied without using team teaching. It means the students who studied by using team teaching could improve their abilities in understanding English narrative text. (3) The students should focus on the study because the teachers observed what they do in the class comprehensively. The student also could receive knowledge not only from the main teacher, but also from the co-teacher and they could ask both teachers if they found some problems. Some advantages of team teaching to the teachers of SMAN 4 Banda Aceh are; team teaching could be effective while teaching and learning process was underway because the teachers could remind each other and they also could plan good materials. In applying team teaching to improve students’ ability in understanding English narrative texts, the teachers used many strategies. One of the general strategies to apply team teaching in SMAN 4 Banda Aceh was by excercising the so called semi team teaching. The special strategies that conducted by teachers were; (1) Presenting an interesting and understandable topic in every meeting for students. (2) Making group discussion, reading the legend and translating it, giving regularly the test and games. (3) Asking the students to comprehend the generic structure of the text before coming to the class.